The isolation Of primary dust explosion between grain mills and Thier storage silos across tunnels (Damascus University Journal for engineering sciences, 2021)
Dust explosions occur in many industrial facilities, including sugar and powdered milk factories, coal mines, drug factories, paper factories, bakeries, grain mills, grain storage silos and many others. By definition, dust explosions are a successive series of primary and secondary explosions, where the primary dust explosion occurs at the beginning, followed by a successive series of secondary dust explosions, which are more dangerous and destructive. The danger of dust explosions and their catastrophic human and physical repercussions are self-evident. They occur as a result of the reaction of flammable dust particles, such as wheat or flour dust, suspended in the air with oxygen, with a source of ignition in a closed chamber.This research aims to explore how to isolate the primary dust explosion and prevent it from spreading and across the tunnels between the grain mills and grain storage silos and reaching the other side and consequently avoiding the occurrence of a series of secondary dust explosions. This will be done through innovative modern scientific and technical solutions by creating reinforced concrete or metal barriers within the tunnel inclined at an angle 150 0 with a thickness of 10 cm and a primary dust explosion vent above the tunnel. The vent is made up of aluminum flakes and a metal grid that breaks open at any slight increase in pressure inside the tunnel exceeding atmospheric pressure to allow the blast and flame waves to come out through the vent and prevent the primary dust explosion from extending to the other side.To this end, a real-life demonstration that simulates what happens in grain mills and grain storage silos was designed and implemented. The demonstration consists of a silo, a mill, a tunnel between them, an electrical ignition coil as a source of spark and an air compressor to distribute dust in a turbulent movement. The aim is to implement experimental tests and show the effectiveness of inclined barriers and vents in isolating the primary dust explosion, preventing its propagation and eventually avoiding the potential successive series of secondary dust explosions. Experimental tests were carried out in two steps: the first was implemented without inclined barriers and vent to show how the primary dust explosion from the silo to the mill passes through the tunnel and turns into a secondary dust explosion, and the second one is made with the presence of barriers within the tunnel inclined at an angle of 1500 from the horizon line and the presence of a vent to exit the blast and flame waves resulting from the primary dust explosion and prevent it from passing from the silo to the mill. The Swedish method, adopted worldwide, was used to calculate the necessary and sufficient vent opening area for the pressure wave to exit according to a mathematical equation. Finally, the experimental results showed that the inclined barriers at an angle of 150 0 within the tunnel, along with the vent to release the pressure and flame waves resulting from the primary dust explosion, were able to isolate the primary dust explosion and prevent it from reaching from the silo to the mill. This modern and innovative method help change the pathway of the pressure and flame waves so as to be released through the vent and out to the surrounding atmosphere, and thus prevent a succession of a series of secondary dust explosions, saving human lives and important economic facilities. In addition, this method is simple, easy to design and cost effective
Keywords: primary dust explosion isolation; series of secondary dust explosions